Enhanced interface properties of solution-processed antimony sulfide planar solar cells with n-type indium sulfide buffer layer. (20th April 2021) - Shi, Junhui; Wang, Yuanqiang; Yang, Mengru; Gu, Yanfang; An, Wei; Men, Yong; Yang, Jingxia; Rui, Yichuan
Highlights: The facile solution-processed methods for preparing Sb2 S3 and In2 S3 films are used. In2 S3 improves the compactness, crystallinity, and optical performance of Sb2 S3 film. In2 S3 buffer layer enhances the photovoltaic characteristics of Sb2 S3 cell device. The promoted charge transfer mobility at TiO2 /In2 S3 /Sb2 S3 interface is determined. Abstract: Although antimony sulfide (Sb2 S3 ) has become a promising photovoltaic material, the performance of Sb2 S3 planar solar cells is pinned by the charge recombination and interface defects of Sb2 S3 thin film . Herein, n-type indium sulfide (In2 S3 ) serving as the buffer layer between TiO2 and the Sb2 S3 layers was prepared by chemical bath deposition (CBD) method. Sb2 S3 thin films were in situ prepared with a solution-processed construction strategy. The characteristics of the obtained thin films were studied in more detail by electron microscopy, X-ray technique, optical and electrochemical performance measurements. Results show that the In2 S3 buffer layer prepared by the optimized CBD time improves the compactness and crystallinity, prevents Sb 3+ from being oxidized, and boosts the light absorption ability for the Sb2 S3 films. The fabricated FTO/TiO2 /In2 S3 /Sb2 S3 /P3HT/Au planar cell device exhibits the higher open-circuit voltage ( Voc ) of 0.59 V, short-circuit current density ( Jsc ) of 8.90 mA cm −2, and power conversion efficiency (PCE) of 2.41%, respectively, compared to the FTO/TiO2 /Sb2 S3 /P3HT/Au cell device. The superior photoelectric conversion performance is attributed to the promoting effects of the In2 S3 buffer layer at the interface between TiO2 and the Sb2 S3 layers, which reduce the charge recombination, facilitate the electron transfer, and enhance the electron lifetime. This work proposes an original insight towards non-toxic In2 S3 as a buffer layer in Sb2 S3 planar solar cells. Graphical abstract: The In2 S3 buffer layer forms a favorable gradient energy band for the TiO2 /In2 S3 /Sb2 S3 plannar solar cell, exhibiting the superior photovoltaic performance compared to the TiO2 /Sb2 S3 cell device. Image, graphical abstract